Review of On the End of Privacy: Dissolving Boundaries in a Screen- Centric World by Richard E. Miller - Kandace Knudson (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
Although I no longer grade student papers, I work closely with students and my faculty colleagues in support of the online learning environment. Need some advice about how to design your online course to increase student engagement? Need to know what the institution’s rules are as they relate to online teaching? Yes, I’m that person: accessibility laws, copyright laws, college policy, how to get this photocopied article into the learning management system, where to click to do this or that.
Keywords: JAEPL